2018
DOI: 10.1007/s00446-018-0329-3
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging multiple channels in ad hoc networks

Abstract: We examine the utility of multiple channels of communication in wireless networks under the SINR model of interference. The central question is whether the use of multiple channels can result in linear speedup, up to some fundamental limit. We answer this question affirmatively for the data aggregation problem, perhaps the most fundamental problem in sensor networks. To achieve this, we form a hierarchical structure of independent interest, and illustrate its versatility by obtaining a new algorithm with linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In real networks, whether one node can communicate with a neighboring node successfully is dependent on many factors, such as environment noises, the sending power energy, the path-loss exponent during transmission, beaconing, and handshaking. The signal-to-interference-plus-noise ratio (SINR) model is a realistic model that captures the collision among multiple transmissions [34]. It is also shown that the SINR model can be converted to the communication graph model that two nodes are neighbors if their distance is within the communication range.…”
Section: Preliminariesmentioning
confidence: 99%
“…In real networks, whether one node can communicate with a neighboring node successfully is dependent on many factors, such as environment noises, the sending power energy, the path-loss exponent during transmission, beaconing, and handshaking. The signal-to-interference-plus-noise ratio (SINR) model is a realistic model that captures the collision among multiple transmissions [34]. It is also shown that the SINR model can be converted to the communication graph model that two nodes are neighbors if their distance is within the communication range.…”
Section: Preliminariesmentioning
confidence: 99%
“…The default assumption is that interference fades with a polynomial of the distance, and transmission succeeds only if the received signal strength is sufficiently larger than the total interference plus noise. Recently, the SINR model has attracted great attentions in the distributed community [6,5,12,21,25,26,27,29,33,34,36,47,51,53,54,55]. Most of these works focus on networks embedded in Euclidean space, while many of the results hold also for doubling or "bounded growth" metrics [5,12,33].…”
Section: A Other Related Workmentioning
confidence: 99%
“…When additionally ∆ is known, this was further improved recently to O(∆ + log n • log log n) in the spontaneous setting [4]. The speedup of multiple channels on local broadcast was considered in [29,55] Broadcast: The complexity of broadcasting is well understood in graph-based models. In the radio network model, Bar-Yehuda et al [3] presented the decay protocol which can accomplish non-spontaneous broadcast in O(D log n + log 2 n) rounds, where D is the diameter.…”
Section: A Other Related Workmentioning
confidence: 99%